Sound Advice: A Consumer's Perspective on Navigating the World of Over-the-Counter Hearing Aids - Katz, James; Mormer, Elaine; Parthasarathy, Aravind; Bharadwaj, Hari; Wang, Yanshan; Palmer, Catherine (Seminars in Hearing, 2025)
This article describes the breadth of experiences associated with pursuing commercially available over-the-counter hearing aids (OTC-HAs). Dr. Katz behaved as a consumer pursuing various OTC-HAs. This activity was part of a larger project aimed at identifying overarching consumer listening goals, creating metrics to assess consumer-identified desired usability, features, and performance, and designing a consumer-friendly web-based application to support thoughtful hearing self-care. Additionally, we provide a review of the aims of the larger project to set the context for this work.
Keywords: over-the-counter hearing aids; amplification; natural language processing; artificial intelligence; large language model